If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10+2n=5(7n+2)
We move all terms to the left:
10+2n-(5(7n+2))=0
We calculate terms in parentheses: -(5(7n+2)), so:We get rid of parentheses
5(7n+2)
We multiply parentheses
35n+10
Back to the equation:
-(35n+10)
2n-35n-10+10=0
We add all the numbers together, and all the variables
-33n=0
n=0/-33
n=0
| 7a=3a+2 | | 5(x+8)=9x+28 | | 2y-7y+5y+29=0 | | 3x^2+12x-525=0 | | 9x+12x-525=0 | | 4(2x+4)-3(5-x)=2x+1 | | 9x+12x=525 | | s+.25=200 | | 25x-8-17x+4=21x-4-13x+12 | | 4t+-6t=10 | | 2x+1=3x-59 | | 12c-3c-6=12 | | 16t^2–24t–16=0 | | 5x+12-9x=15-19x+15x-3 | | 2x-25+5x=7-32 | | x−3=4 | | 16t^2-24t-16=0 | | X^4+4x^2-27=0 | | 2x/50=4/x | | 3a(a+2)+1=0 | | x/100=0.185 | | 14=x-7/8 | | -x+7=-2x+5 | | 3(x-12)-3x=112 | | 2x+7=-3x+52 | | 16-3x=3x+40 | | 48=30(3.6)+b | | 2=25(288)+b | | 3-2x+7=5x-4 | | (4-y)/3=6 | | 7/5+4/5x=53/20+7/4x+1/4 | | 48+6+3x=90 |